Estudio geológico y análisis estructural de las vetas mineralizadas de interés económico definidas sobre las galerías Pillacela y Montesdeoca del Área de Concesión Minera Mimopi código: 264” ubicada en la provincia de El Oro, cantón Zaruma - Solano Salinas, Henry Vinicio (2019)
Mining company MINERMIR S.A is a small mining company that develops exploration and exploitation activities within the MIMOPI Code mining concession. 264, It is located in the Zaruma canton, is 4km away by the road to Rome / Sinsao / Ortega / Salvias, forming part of the Zaruma Portovelo polymetallic gold district, which has been developed since colonial times. The mining area consists of 18 hectares where there are 2 different bocamina, Montesdeoca in coordinates (655165; 9593180) at elevation of 1266 m.s.n.m and Pillacela at coordinates (655219; 9593118) at elevation 1236 m.s.n.m. This research topic is based on the study and correlation of the Amarilla and Miranda mineralized veins located in the N-S direction that are cut by the mining fronts. The present investigation includes lithological analysis (Mapping of geological units), structural, mineralogical analyzes that allow to determine the paragenesis and textures and stays of the same. Mineralization is distinguished by being present in vetiform structures associated with low sulfurization hydrothermal deposits, where mineralization is housed in porphyry andesite rocks, afanitic andesites and basaltic andesites belonging to the Portovelo Unit. Mainly, propylitic and philic alteration are identified, with oxidation of iron and hematite minerals affecting the box and grain rock. The veins under study go longitudinally N-S, have a rich carbonate mineralogy; malachite (Mq), rich in primary sulphides; cyrite (Py), chalcopyrite (Cape), galena (Gn), and secondary sulphides; calcosina (Cc), covelita (Cv) themselves that have been formed by the alteration of primary sulfides. The mineralization has quartz textures with massive sulphide, milky massive quartz, textures in crustiform-coloform bands. Keywords: Geological Units, paragenesis, hydrothermal deposits, crustiform-coloform textures.